STRATEGI PENINGKATAN KINERJA UKM PEMBUATAN TERASI DI KABUPATEN REMBANG - Maslichan Maslichan; Dian Ayu Liana Dewi (BBM (Buletin Bisnis & Manajemen), 2017)
This research aims to analyze and prove the factors that directly affect their business strategy in order to improve the performance of the terasi production in the district of Rembang and to analyze and prove the factors that directly affect business strategy in order to improve the performance of the terasi production in the district of Rembang. Respondents in this study were managers or owners of terasi production in the district of Rembang. The analysis technique uset test track path. The results of this study concluded that education, skill, and environmentally significant positive effect on improvement of the business strategy of terasi production in the district of Rembang. As well as education, skills, and environment as well as good business strategy will accelerate the improvement of business performance of terasi production in the district of Rembang.Keywords: performance improvement, the business strategy, education, skills and the environment.